Transient total blindness associated with alcoholic ketoacidosis. Issue 1 (11th May 2021) - Sato, Hiroki; Kyan, Ryoko; Kamada, Chinami; Kaku, Mitsunori; Sato, Shota; Tawara, Toshihiro; Sakawaki, Eiji; Sakawaki, Sonoko; Takeyama, Yoshihiro
Abstract : Background: Methanol poisoning is often suspected in patients with high anion gap metabolic acidosis and visual deficits. Although alcoholic ketoacidosis can cause high anion gap metabolic acidosis, reports on vision loss are limited. We report the case of a patient with alcoholic ketoacidosis with transient total blindness. Case Presentation: A 56‐year‐old man complaining of total blindness was transferred to our hospital. Physical examination revealed a clear consciousness and mydriasis with an absence of pupillary light reflex. Blood analysis revealed high anion gap metabolic acidosis with a high ketone body concentration. Alcoholic ketoacidosis was diagnosed because the patient had a chronic alcohol abuse history and denied methanol intake. As acidemia improved because of fluid infusion and glucose and vitamin B1 supplementation, his visual acuity recovered. He was discharged after 44 days without visual deficits. Conclusion: Patients with alcoholic ketoacidosis may present with acute vision loss, which recovers along with treatment. Abstract : A case report of transient blindness associated with alcoholic ketoacidosis and the summary of reported cases of vision loss associated with acidemia.